Identification of HLA-C restricted, HIV-1-specific CTL epitopes by peptide induced upregulation of HLA-C expression - Stoll, Andrej; Bergmann, Silke; Mummert, Christiane; Mueller-Schmucker, Sandra M.; Spriewald, Bernd M.; Harrer, Ellen G.; Harrer, Thomas (Journal of Immunological Methods, 2015)
HIV-1 negative regulatory factor (Nef) can inhibit CTL recognition by downregulation of HLA-A and HLA-B on the cell surface. In contrast, HLA-C is not affected by Nef and a growing number of studies demonstrate an important role of HLA-C for the control of HIV-1. So far, only a limited number of HLA-C restricted CTL epitopes are known. As the mapping of new CTL epitopes is time and labor intensive, we investigated a novel method for the identification of HLA-C restricted CTL epitopes. B-lymphoblastoid cell lines (B-LCLs) and T2-cells were incubated with HIV-1 specific peptides and subsequently stained for HLA-C surface expression using the HLA-C specific antibody DT9. Peptides that led to increased HLA-C surface expression were used for stimulation of PBMC from HIV-1-infected patients. Subsequently, outgrowing cells were tested for peptide recognition in IFN-? ELISPOT assays and HLA restriction of the recognized peptides was analyzed in ELISPOT assays using HLA-matched B-LCL. We observed that known HLA-C binding peptides increase HLA-C surface expression on T2-cells and on HLA-C*0102 and HLA-C*0702 homozygous B-LCL. Moreover, screening of HIV-1 Nef with overlapping peptides for potential C*0702 restricted epitopes using this method revealed a total of 8 peptides which considerably increased cell surface expression of HLA-C. By epitope mapping and functional analysis of peptide-stimulated T-cell lines we were able to define the peptide YPLTFGWCY as a new C*0702-restricted CTL epitope. These results show that the analysis of peptide induced HLA-C upregulation on B-LCL and T2-cells enables the efficient identification of new HLA-C restricted CTL epitopes.
EVALuna2:13104